Synergistic inhibition of cerium and alkyl phosphate composite adlayer on pitting corrosion of Al–Mg–Si aluminium alloy. (3rd October 2021) - Sun, Xiaoguang; Cao, Xiangkang; Zhang, Zhiyi; Han, Xiaohui; Ruan, Hongmei; Dong, Zehua
ABSTRACT: The nucleation, propagation, and rehabilitation of pitting corrosion of Al–Mg–Si Aluminium alloy (AA6063) are studied in 3%NaCl solution by using electrochemical noise measurement. It shows that the composite film composed of sequent precipitation of ceria and 1-tetradecylphosphonic acid (DPA) presents the best pitting corrosion resistance compared with the independent ceria conversion film or self-assembling DPA film. XPS and microscopic Raman spectra confirmed that Ceria film is an excellent interlayer for the self-assembling of alkyl phosphate on the intermetallic particles in Al alloy. The anti-corrosion performance of Cerium oxides and DPA composite film is totally dependent on the deposition sequence. Prior deposition of ceria and then DPA film can increase the hydrophilicity of Al matrix and AlFeSi intermetallic particles, further promoting the self-assembling of upper DPA molecules, thus dramatically improving the overall and pitting corrosion resistance of AA6063. This could be attributed to the synergistic effects between the upper DPA film and underlying Ce conversion film. On the contrary, Prior assembly of DPA and then deposition of ceria, may significantly degrade their inhibition efficiency.